2012
DOI: 10.1097/hjh.0b013e32835821e5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological assessment of renal arteries after radiofrequency catheter-based sympathetic denervation in a porcine model

Abstract: Catheter-based application of radiofrequency energy resulted in circumscribed transmural injury within the arterial wall affecting autonomic nerve fascicles delayed to treatment. Acute loss of endothelialization resulted in thrombus formation leaving kidney perfusion apparently unimpaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
51
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 18 publications
11
51
4
1
Order By: Relevance
“…Although angiography results showed there were slight vessel irregularities caused by radiofrequency energy delivery, the lesions disappeared at first month of follow-up. Our angiography results were similar to those of the study by Steigerwald et al 31 which conducted RDN using the Symplicity Catheter System. In Simplicity trials, renal artery aneurysm or stenosis was seldom seen as judged by computed tomography (CT) or magnetic resonance imaging (MRI) angiography.…”
Section: Renal Angiogramsupporting
confidence: 90%
“…Although angiography results showed there were slight vessel irregularities caused by radiofrequency energy delivery, the lesions disappeared at first month of follow-up. Our angiography results were similar to those of the study by Steigerwald et al 31 which conducted RDN using the Symplicity Catheter System. In Simplicity trials, renal artery aneurysm or stenosis was seldom seen as judged by computed tomography (CT) or magnetic resonance imaging (MRI) angiography.…”
Section: Renal Angiogramsupporting
confidence: 90%
“…18 It is not surprising that there was absence of arterial endothelial damage at 7 days after treatment in the current study because re-endothelialization has previously been reported to be complete within 10 days in other preclinical RDN studies. 11 Although recent optical coherence tomography imaging studies observed occasional small nonocclusive mural thrombi in the renal arteries after RDN procedures, 19 it is clear from the HTN-3 study 9 that the RDN procedure was safe. On a morphological level, the current study showed that nerve regeneration was observed within the region of radiofrequency ablation and yet, complete neuronal restoration was absent at 180 days.…”
Section: Discussionmentioning
confidence: 99%
“…Although local loss of the endothelium was observed in the hyperacute phase, arterial media injury and nerve degeneration such as vacuolization and perineural fibrosis were only observed in the subacute phase. 11 Rippy et al 10 only investigated the histopathologic findings after radiofrequency RDN at 6 months (chronic phase) in the swine model using the Symplicity RDN system. Renal nerve injury was characterized as healing fibrosis causing a thickening of the surrounding perineurium in affected nerves.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol is unlikely to change as long as the experimental treatment is delivered via a transarterial, catheterbased platform. Ultrasound (US), computed tomography (CT) angiography, and magnetic resonance (MR) angiography all may be useful for screening and planning before RDN, but the relative benefit of these noninvasive imaging modalities needs to be evaluated further and validated (47,48).…”
Section: Rdn In the Presence Of Renal Artery Stenosismentioning
confidence: 99%